Derma menurut Pandangan Etika Belas Kasih Arthur Schopenhauer dan Gereja Katolik - Fatlolon, Costantinus; Ulahayanan , Aloysius (Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
This study applies a descriptive-critical approach to the ethical beliefs of Arthur Schopenhauer and the Catholic Church on charity. The fundamental research question is: “What are the similarities and differences between Schopenhauer’s and the Catholic Church’s views on charity?